Content validity of the quality of dying and death questionnaire- revised global-version in North American inpatient hospices - Alyssa E. Tilly; Jared E. Lowe; Mary Goombs; Manokaraananthan Chandrakumar; Nadine Persaud; Sarah Hales; Argin Malakian; Camilla Zimmermann; Kayla Wolofsky; Gary Rodin (PLoS ONE, 2026)
Context Enhancing end-of-life care requires valid measurement of the quality of dying and death, but existing measures of this outcome have limited applicability across varied cultural and resource settings. To address this gap, we revised the Quality of Dying and Death Questionnaire (QODD) to create the QODD-Revised Global Version (QODD-RGV). Objectives Our objective was to conduct a preliminary evaluation of the content validity of the QODD-RGV questionnaire in North American inpatient hospice settings based on item relevance, comprehensibility, and comprehensiveness. Methods Bereaved caregivers of patients who died in inpatient hospices in Canada and the United States were recruited 4–6 months after death of the patient. Participants completed the QODD-RGV, a 26-item measure assessing the experience of patients in the last week of life regarding symptoms, care preferences, and social support. Cognitive interviews were conducted with verbal probing and think-aloud techniques to evaluate the participants’ understanding of the items and the information they relied upon to make their ratings. Interview transcripts were coded independently by two team members followed by consensus coding. Qualitative content analysis was performed. Results Eighteen cognitive interview protocols were completed. Participants indicated that their ratings were most commonly based on information from the perspective of the patient or themselves. The most common judgment strategy was comparison to “a hoped for or ideal dying experience,” followed by “a state of distress/no distress.” All respondents used multiple standards of comparison. Response difficulty was most frequently due to lack of communication with the patient. No single item was consistently misunderstood, but there was uncertainty about the ratings of some items due to limited caregiver knowledge or time spent communicating with the patient. Conclusion The present study with bereaved caregivers in North American inpatient hospice settings provides preliminary evidence supporting the content validity of the QODD-RGV in North American hospice settings based on relevance, comprehensibility, and comprehensiveness of the items.